Vuoti d’immagine: rimozioni e false memorie (ENTHYMEMA, 2022)
The paper investigates mechanisms of removal and false memories in phototextual narratives. In particular, I will propose a typology capable of categorising the ways in which oblivion takes artistic form through various ways of excluding an image from the reader's field of vision. The photos thus leave an interpretative space for readers, who find themself in front of an enigmatic situation continuously questioned by the word.
Keywords: Oblivion; Memory; Photo-text; Photography; Visual Culture